Responding to Monetary Authority Interest Rate Policy: Performance, Financial Risk, and Operational Efficiency Analysis of Commercial Banks - Muhammad Faisal; Slamet Muchsin; Afiffudin Afiffudin; Nur Indira Maharani; Denny Rakhmad Widi Ashari (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
Interest rate policy plays an important role in influencing financial risk and bank performance, especially in emerging economies with high economic volatility. The objective of this research is to study how interest rate policy, credit risk, liquidity risk, and bank performance interact with each other in a complex way. This is done by considering both internal and external variables. This research analyzes literature from a number of international empirical studies focusing on developing and developed countries. The data is analyzed to find patterns and relationships between interest rate policy and bank financial risk. The results show that lower interest rates increase credit risk through aggressive loan expansion and lower credit standards. Declining interest rates also increase liquidity risk as depositors' incentives are reduced. In addition, it was found that good capital structure and governance can mitigate the negative effects of interest rate fluctuations on bank performance. This research strengthens the theoretical basis on the role of monetary policy in the banking industry and emphasizes macroprudential regulation and adaptive risk management strategies. Further research is suggested to include negative interest rate policies or global financial markets, but practical implications include the need for policies that support financial stability amid low interest rate challenges.